DETERMINAN HARGA SAHAM LQ45 PADA MASA PANDEMI COVID-19 - Ni Putu Yuliana Ria Sawitri (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2022)
The stock price is a reflection of investors' expectations of financial factors such as income, cash flow, and returns that are expected by investors, all of which are influenced by the macro conditions of a country as well as global economic conditions. Changes in share prices are largely determined by market conditions, namely from the demand for shares by investors. The decision to buy and sell shares in the capital market by investors is carried out using fundamental analysis and technical analysis. A long-term investment is carried out using fundamental analysis, namely analyzing the company's financial performance. Financial performance can be seen from three factors, namely Debt to Equity Ratio (DER), Dividend Per Share (DPS), and Return on Assets (ROA). The purpose of this study was to examine the partial and simultaneous effect of DER, DPS, and ROA on stock prices in companies listed on the LQ45 index for the 2016-2020 period. The research data was tested using multiple linear regression analysis. The results showed that if DER has a positive and insignificant effect on stock prices, DPS has a positive and significant effect on stock prices, ROA has a negative and significant effect on stock prices. The final test results found that DER, DPS, and ROA simultaneously influence the stock price of the LQ45 company for the 2016-2020 period.